Early embryonic mutations reveal dynamics of somatic and germ cell lineages in mice - Uchimura, Arikuni; Matsumoto, Hirotaka; Satoh, Yasunari; Minakuchi, Yohei; Wakayama, Sayaka; Wakayama, Teruhiko; Higuchi, Mayumi; Hashimoto, Masakazu; Fukumura, Ryutaro; Toyoda, Atsushi; Gondo, Yoichi; Yagi, Takeshi (Genome Research, 2022)
De novo mutations accumulate with zygotic cell divisions. However, the occurrence of these mutations and the way they are inherited by somatic cells and germ cells remain unclear. Here, we present a novel method to reconstruct cell lineages. We identified mosaic mutations in mice using deep whole-genome sequencing and reconstructed embryonic cell lineages based on the variant allele frequencies of the mutations. The reconstructed trees were confirmed using nuclear transfer experiments and the genotyping of approximately 50 offspring of each tree. The most detailed tree had 32 terminal nodes and showed cell divisions from the fertilized egg to germ cell– and somatic cell–specific lineages, indicating at least five independent cell lineages that would be selected as founders of the primordial germ cells. The contributions of each lineage to germ cells and offspring varied widely. At the emergence of the germ cell–specific lineages, 10–15 embryonic mutations had accumulated, suggesting that the pregastrulation mutation rate is 1.0 mutation per mitosis. Subsequent mutation rates were 0.7 for germ cells and 13.2 for tail fibroblasts. Our results show a new framework to assess embryonic lineages; further, we suggest an evolutionary strategy for preserving heterogeneity owing to postzygotic mutations in offspring.